School and Parent Collaboration through the SOBAT Program in Tackling Student Bullying - Rachmawati, Dwi Wahyu; Sholeh, Muhamad; Rifqi, Ainur (Lectura : Jurnal Pendidikan, 2025)
Bullying, a persistent form of violence in schools that harms students' mental health and character development, requires collaborative efforts between parents and schools, especially within Indonesia's current educational focus on strengthening supportive learning ecosystems. This study aims to analyze the effectiveness of the Great School Parents Program (Sekolah Orang Tua Hebat Program/SOBAT) in building partnerships between schools and parents to reduce bullying cases at Junior High School (Sekolah Menengah Pertama/SMP) Negeri 1 Singojuruh Banyuwangi. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation, then analysed using data reduction, data presentation, and conclusion-drawing techniques. The results of the study indicated that the SOBAT Program successfully created synergy between schools and parents in shaping students’ character, improving early detection of bullying behavior, and strengthening the role of families in positive parenting. The activities implemented included parenting classes, family discussion forums, counseling services, and digital communication. The impact was evident in the decrease in bullying cases and the increase in students’ openness and parents’ concern for their children’s psychosocial conditions. However, time constraints and parents’ lack of understanding regarding the urgency of their role remain major challenges. In conclusion, this study emphasizes that parental involvement is not merely a supporting element but a strategic key in character education transformation. This program holds significant potential for contextual replication across various educational institutions as a collaborative model in building sustainable child-friendly schools.